The Role of Driving Teachers in Developing Differentiated Learning Strategies And Social-Emotional Competencies in Integrated Social Studies Subjects - Girsang, Herti; Corry, Corry; Arent, Ease (Jurnal Indonesia Sosial Sains, 2025)
The evolving landscape of education demands innovative teaching practices, with Guru Penggerak playing a pivotal role in implementing differentiated learning strategies and fostering students’ social-emotional competencies, particularly in Integrated Social Studies. This study aims to explore how Guru Penggerak contributes to creating inclusive and adaptive learning environments that respond to students' diverse characteristics while supporting their emotional and interpersonal development. A qualitative research design was employed, using document analysis from academic journals, official reports, and relevant literature to identify key practices, enabling factors, and barriers encountered in the field. The findings reveal that the success of differentiated instruction is largely influenced by the teacher's ability to recognize and respond to varied learning styles. Approximately 70% of students reported increased motivation when instructional strategies aligned with their individual preferences. Additionally, structured efforts to build social-emotional competencies resulted in enhanced student well-being, classroom harmony, and increased engagement. These findings highlight the importance of empowering teachers through continuous professional development to strengthen their pedagogical and socio-emotional facilitation skills. The study provides valuable insights for educational stakeholders to support Guru Penggerak programs and reinforce the integration of differentiated learning and emotional intelligence in curriculum implementation.